(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
To evaluate the relationship between maternal weight gain and fetal weight in term pregnancy. An observational study was carried out in a private clinic in Cox’s Bazar, from March 2011 to March 2012. Total 200 mothers with singleton pregnancy were selected. Maternal weights were recorded in 1st trimester and 3rd trimester. Fetal weights were noted at 37 completed weeks of gestation by ultrasonography. Most (63%) of the women were 20 - 29 years of age (mean 24.1±5.3) and 70.5% women got married at the age of 16 — 20 years (mean 18.71±2.79) and 11% of them had <2500gm fetus. The frequency of <2500gm fetus were 12% and 22.5% had > 1 children (mean 1.33±0.36), 46% of mothers having >3 children had <2500gm fetus (p = <0.05). It was detected that 65.5% of 20 — 24 years old mothers gained 10-12 kg. Mothers who gained < 8 kg of weight, 75% of them had <2500gm fetus, this study also revealed that 44.3% of mothers who gained 10 -12 kg weight had>2500gm fetus. There is significant correlation between the number of parity and variation of fetal weight. JCMCTA 2014 ; 25 (2) : 31-35